Rational Emotive Counseling Based On Krishna-Arjuna Conversation In Treating Stress In The Covid-19 Pandemic - Rasmini, Ni Wayan; Weda, I Gustti Lanang Ngurah; Wibawa, I Gede Jaya Satria (LPPM Undiksha, 2023)
The COVID-19 pandemic has claimed many lives and resulted in stress in some communities. This study aims to analyze the implementation of Krisna-Arjuna conversation-based emotional-rational counselling in coping with anxiety due to the COVID-19 pandemic. This research is based on Miles and Huberman's qualitative research model with a case study design. 125 people were targeted, and 30 experienced stress due to the COVID pandemic (16 were in the mild category, 9 were moderate, and 5 were in the heavy class). Data were collected utilizing observation, interviews, and documents. The data obtained is in the form of qualitative data that has been credibly tested for validity. Then a qualitative analysis is carried out, starting with data presentation, reduction, and verification/conclusion. The findings of this study are the design of Krishna-Arjuna conversation-based emotional-rational counselling to deal with the stress of COVID-19. Providing information, group counselling, and individual counselling to prevent and treat symptoms of COVID-19 stress with a limited level of understanding and age heterogeneity has positive implications for the prevention and management of COVID-19 stress. It is hoped that individuals, families, communities, and related parties will study and apply rational-emotive counselling to overcome irrational thought patterns and deal with stress.